Near Eastern Archaeology in Historic Photographs - O'Reilly, Ingeborg Endter (The Biblical archaeologist, 1983)
During the nineteenth century early photographers recorded sites in the Holy Land that would soon be changed forever. At the turn of the century the pioneers of scientific excavation in the region used photography to document their work. The photographs of both groups are now recognized as important archaeological tools.